2015
DOI: 10.1097/moo.0000000000000130
|View full text |Cite
|
Sign up to set email alerts
|

Update on surgical management of adult inferior turbinate hypertrophy

Abstract: Inferior turbinate surgery offers benefit and improves nasal obstruction in patients with hypertrophic inferior turbinate refractory to medical treatment. Rigorously designed study including subjective and objective measurements, control or comparison group, and long-term follow-up should be carried out in the future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
0
21
0
1
Order By: Relevance
“…Both studies concluded that surgery of the turbinates offered improvement of nasal obstruction in patients with inferior turbinate hypertrophy refractory to medical therapy; however, given the scarcity of level 1 and 2 data, they also indicated that further prospective studies should privilege randomization, inclusion of control groups, rigorous prestudy methodology, and the use of validated instruments to assess the results as applied in the present study. 44,45…”
Section: Discussionmentioning
confidence: 99%
“…Both studies concluded that surgery of the turbinates offered improvement of nasal obstruction in patients with inferior turbinate hypertrophy refractory to medical therapy; however, given the scarcity of level 1 and 2 data, they also indicated that further prospective studies should privilege randomization, inclusion of control groups, rigorous prestudy methodology, and the use of validated instruments to assess the results as applied in the present study. 44,45…”
Section: Discussionmentioning
confidence: 99%
“…Mientras que los medicamentos actúan únicamente en los tejidos blandos, la cirugía puede actuar sobre éstos, la estructura ósea o ambos. Las cirugías incluyen la lateralización o outfracture; resección submucosa del hueso conchal; resección submucosa con microdebridador; reducción submucosa con radiofrecuencia, electrocauterización u otros; y la turbinectomía parcial 15,16 . En general, las turbinectomías totales son poco utilizadas para esta indicación debido al mayor riesgo teórico de alterar la función nasal, rinitis atrófica y síndrome de nariz vacía [17][18][19][20] .…”
Section: Cirugía De Los Cornetes Inferioresunclassified
“…Inferior turbinate reduction (ITR) treats ITH by decreasing nasal obstruction, thereby increasing nasal airflow and improving patients' subjective sense of patency [3]. Current reduction techniques include turbinectomy (total and partial), turbinoplasty (outfracture, submucous resection, and microdebrider), thermal procedures (electrocautery and radiofrequency ablation), and laser surgery [4].…”
Section: Introductionmentioning
confidence: 99%
“…An established optimal procedure is not yet identified. The ideal surgical treatment for ITH should alleviate symptoms by achieving significant volume reduction while preserving mucosal function, but no clear consensus exists in the literature with respect to methods or device to accomplish this objective [4,5]. In their 35‐year review of the otolaryngology literature published in 2001, Clement and White [16] did not identify any randomized controlled studies of inferior turbinate surgery for nasal obstruction.…”
Section: Introductionmentioning
confidence: 99%